Penerapan Tahdzir dan Hajr dalam Dakwah Salafi: Persfektif Eksternal dan Internal - Ayyub; Aswan Malaba; Hasan Basri; Mansur; Rahmawati (Gunung Djati Conference Series, 2022)
This article discusses how to apply Tahdzir and Hajr in Salafi da'wah from external and internal perspectives. The method in this research is using data triangulation technique. Based on the results of research conducted on Dai and the salafi congregation, it was found that the purpose of salafi applying the tahdzir and hajr methods was as a form of da'wah efforts in enforcing amar makruf nahi munkar, when they found deviations in terms of creed and practice that were not found in the salafushshaleh generation. The application of tahdzir and hajr is not only limited to external salafi groups, but internal salafis can also be applied when they have deviated from the salaf manhaj. As for the application of tahdzir in the form of reprimands and warnings addressed to dai and religious groups deemed deviant; while the form of hajr is the severance of muamalah relations with deviant mad'u, by not socializing, speaking, listening to the contents of lectures and not have assemblies. The basis for its application from an external point of view is based on the principles of tahdzir and hajr da'wah written in books, lectures and fatwas of local salafi preachers, while internally following the fatwas of major international salafi scholars.